1990
DOI: 10.1128/iai.58.5.1240-1246.1990
|View full text |Cite
|
Sign up to set email alerts
|

Antibody responses to Toxoplasma gondii in sera, intestinal secretions, and milk from orally infected mice and characterization of target antigens

Abstract: Toxoplasma gondii-specific antibody responses in serum, intestinal secretions, and milk were identified with an enzyme-linked immunosorbent assay following a single oral infection of mice with strain 76K cysts of T. gondii. Immunoglobulin A (IgA) production began during week 2 of infection in serum and milk and during week 3 of infection in intestinal secretions and persisted in all three throughout the experiment (17 weeks). IgG but not IgM antibodies were detected in intestinal secretions later in the infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
3

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(35 citation statements)
references
References 22 publications
(22 reference statements)
1
31
0
3
Order By: Relevance
“…[26][27][28][29] Different studies have shown specific antibodies in the intestinal mucosa, milk and tears, supporting the idea that these local responses have a protective role. 25,30 In this context, several murine models have demonstrated that the nasopharynx-associated lymphoid tissue (NALT) and the gutassociated lymphoid tissue (GALT) promote an effective protection against T. gondii antigens locally and systemically. 27,31 In humans, NALTs, such as adenoids and palatine tonsils, have been considered more important than GALT as the sites for induction of B cells, which produce antibodies destined for the salivary which reduces the need for pro-inflammatory systemic immunity to eliminate invading infectious agents and other exogenous antigens.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29] Different studies have shown specific antibodies in the intestinal mucosa, milk and tears, supporting the idea that these local responses have a protective role. 25,30 In this context, several murine models have demonstrated that the nasopharynx-associated lymphoid tissue (NALT) and the gutassociated lymphoid tissue (GALT) promote an effective protection against T. gondii antigens locally and systemically. 27,31 In humans, NALTs, such as adenoids and palatine tonsils, have been considered more important than GALT as the sites for induction of B cells, which produce antibodies destined for the salivary which reduces the need for pro-inflammatory systemic immunity to eliminate invading infectious agents and other exogenous antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Other parasites that infect their hosts through the intestinal mucosa also trigger the production of specific secretory IgA (Davis & Porter 1979, McLeod & Mack 1986, Chardès et al 1990) and it has been shown that mucosal IgA can protect against infection with Emeria tenella by inhibiting penetration of the parasite into host cells (Davis & Porter 1979). IgA antibodies also have two other immunological functions in addition to their major role in extracellular defence, one is immune exclusion (McLeod & Mack 1986) and the other is intracellular neutralization of pathogens (Mazanec et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In experimental rodent models, oral infection induces early IgA antibodies in intestinal secretions, differing in kinetics from those of IgG, IgA and IgM in milk and serum (58,59).…”
Section: Mucosas and Secretionsmentioning
confidence: 99%